Incidence and Risk Factors of Gestational Diabetes Mellitus: A Prospective Cohort Study in Qingdao, China - Li, Guoju; Wei, Tao; Ni, Wei; Zhang, Ai; Zhang, Jun; Xing, Yuhan; Xing, Quansheng (Frontiers in Endocrinology, 2020)
Background: Obesity and maternal age are the two most important factors independently affecting the risk of gestational diabetes mellitus(GDM). However, the age differences in the association between obesity and GDM remain unclear. The objectives of this cohort study included: (1) to determine the current incidence of GDM in Qingdao; and (2) to evaluate the risk factors for GDM, such as the interaction between pre-pregnancy body mass index (BMI) and age. Methods: The cohort included 17,145 pregnant women who registered at 15 to 20 gestational weeks from August 1, 2018, to March 1, 2019. A 75-gram 2-hour oral glucose tolerance test (OGTT) was conducted for each participant at 24–28 gestational weeks. The age-adjusted incidence of GDM was calculated using logistic regression. Multivariate logistic regression analysis was used to identify risk factors. Interaction between age (reference group < 30 years) and BMI (reference group < 25 kg/m2) was determined using strata-specific analysis. Results: The incidence and age-adjusted incidence of GDM in Qingdao were 17.42% and17.45%, respectively. The incidence of GDM appeared to increase steadily with age in all pre-pregnancy BMI groups (all P for trend <0.05). Older age (≥ 30 years), gestational BMI gain from pre-pregnancy to 15–20 weeks of gestation, history of GDM and thyroid diseases were risk factors for GDM. There were significant interactions between pre-pregnancy BMI and age (P < 0.05) after adjustment for other confounders. The odds ratio (OR) of pre-pregnancy BMI ≥ 30kg/m2 at the age of < 30 years, 30–34 years and ≥ 35 years was 1.30 (95%CI: 0.74–2.28, P = 0.36), 3.21 (95%CI: 2.28–4.52, P < 0.0001) and 1.55 (95%CI: 1.02–2.36, P = 0.0424), respectively. This indicated that pre-pregnancy BMI ≥ 30kg/m2 had a stronger effect on GDM in the group aged 30-34 years than those under 30 years old. Conclusions: The incidence of GDM was high in Qingdao. Overweight and obesity prior to pregnancy, gestational BMI gain from conception to 15–20 weeks of gestation and older age were correlated with an increased risk of GDM. Public health measures may be helpful to prevent excessive gestational weight gain.